HARVESTER’S– A FIELD EXPERIENCE AS A NUTRITION INTERN - Shafer, Aundrea (My University, 2013)
This report highlights my experience as a nutrition services intern at Harvester's located in Kansas City, Missouri. The field experience was completed as one of the requirements for the Master of Public Health at Kansas State University. During the spring and summer of 2013 I worked with Ms. Taryn Glidewell, the Nutrition Services Manager at Harvester's. My involvement in various community outreach nutrition activities offered through Harvester's and the surrounding communities improved my public health experience. I worked on a variety of projects and endeavors throughout the Nutrition Services Department with the major project focusing on creating a new curriculum for one of the child nutrition programs called Kid's Cafe to be used in the upcoming school year and offered in a variety of community settings throughout Kansas City. This field experience allowed me to work with a vast array of individuals who differed in ethnicity, age, educational levels, gender, income levels, geographic setting, etc. Direct work with nutrition education allowed me to utilized my core coursework and create educational lessons to be used in a variety of settings with children enrolled in the Kid's Cafe program and enable children in a wide array of areas to make better nutritional choices.
Keywords: Harvester's food bank; Nutrition services; Public Health (0573)